Genetic structure of indigenous sheep breeds in Nigeria based on electrophoretic polymorphous systems of transferrin and haemoglobin (2018)
The study used 100 indigenous sheep comprising 25 Balami, 25 Uda, 25 Yankassa and 25 West African Dwarf breeds reared extensively. The blood samples were taken from Vena Jugularis, processed according to standard procedure and transferrin and haemoglobin examined using cellulose acetate electrophoresis. The observed allele frequencies and genotypes (%) were tested with Hardy-Weinberg’sEquilibrium (χ2). Seven alleles TfA, TfB, TfC, TfD, TfE, TfGand TfPcontrolling 23 genotypes were observed at the transferrin locus while two haemoglobin alleles (HbAand HbB) controlling three phenotypes HbAA, HbAB and HbBB were detected. Except for the West African Dwarf sheep, all the samples indicated genetic equilibrium revealed by significant difference between observed and expected genotypes at both loci. The observed significant difference between the frequencies of alleles and genotypes at the two studied loci in the West African Dwarf sheep can be used as a source of genetic diversity during selection for improvement. The phylogenetic analysis as viewed by the tree topology suggests that the Balami and Uda may have had the same migration route or may have been the same breed which hadonly just recently branched off through adaptive. Also, the West African Dwarf sheep may have been the first to branch off the path of migration and thus had more clearly defined migration route or origin.